2017
DOI: 10.1007/s00198-017-4151-8
|View full text |Cite
|
Sign up to set email alerts
|

Osteosarcopenia: where bone, muscle, and fat collide

Abstract: As the world's population ages, the prevalence of chronic diseases increases. Sarcopenia and osteoporosis are two conditions that are associated with aging, with similar risk factors that include genetics, endocrine function, and mechanical factors. Additionally, bone and muscle closely interact with each other not only anatomically, but also chemically and metabolically. Fat infiltration, a phenomenon observed in age-related bone and muscle loss, is highly prevalent and more severe in sarcopenic and osteoporo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
336
0
44

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 376 publications
(403 citation statements)
references
References 88 publications
4
336
0
44
Order By: Relevance
“…Maugeri and colleagues suggest that the release of inflammatory cytokines including IL‐6 and TNF‐alpha from both marrow and body fat could contribute to this lipotoxicity causing osteo‐ and sarcopenia . This notion has also been supported by Ng and Duque and recently reviewed by Hirschfeld …”
Section: Discussionmentioning
confidence: 86%
“…Maugeri and colleagues suggest that the release of inflammatory cytokines including IL‐6 and TNF‐alpha from both marrow and body fat could contribute to this lipotoxicity causing osteo‐ and sarcopenia . This notion has also been supported by Ng and Duque and recently reviewed by Hirschfeld …”
Section: Discussionmentioning
confidence: 86%
“…Sarcopenia, osteoporosis, and osteosarcopenia can be considered part of frailty (Hirschfeld et al, 2017). Frailty is associated with chronological age (Bassey and Harries, 1993), but Syddall et al (2003) demonstrated an even stronger association between frailty and (decreased) age and gender stratified HGS.…”
Section: Hip Fracture Hand Grip Strength and Frailtymentioning
confidence: 99%
“…Two of those ageing related conditions are osteoporosis and sarcopenia. They have similar risk factors and often occur simultaneously, then referred to as osteosarcopenia (Hirschfeld et al, 2017). Osteoporosis is an undisputed major risk factor for sustaining a hip fracture.…”
Section: Hip Fracture Hand Grip Strength and Frailtymentioning
confidence: 99%
See 1 more Smart Citation
“…These are associated with similar risk factors including genetics, endocrine function, and mechanical factors. 35) Individuals with a combination of both disorders, called 'sarco-osteoporosis,' are at the greatest risk of falls and fractures. 36,37) …”
Section: Sarco-osteoporosismentioning
confidence: 99%